Building a Culture of Peace through Peace Education as the Foundation for Merdeka Campus Transformation - Irawan, Hendri; Tutik Wijayanti; Satrio Alpen Pradanna; Anif Istianah (Universitas Negeri Semarang, 2024)
Higher education is a crucial foundation for shaping individuals who are both high-quality and positively contribute to society.This study reviews the transformation of peace education within the Merdeka Campus environment, an innovative approach in Indonesia's higher education system. The